Poststroke action slowing: Motor and attentional impairments and their imaging determinants. Evidence from lesion-symptom mapping, disconnection and fMRI activation studies. (15th December 2022) - Ouin, Elisa; Roussel, Martine; Aarabi, Ardalan; Arnoux, Audrey; Tasseel-Ponche, Sophie; Andriuta, Daniela; Thiebaut de Schotten, Michel; Toba, Monica N.; Makki, Malek; Godefroy, Olivier; ,
Abstract: Background and objectives: Although action slowing is the main cognitive impairment in stroke survivors, its mechanisms and determinants are still poorly understood. The objectives of the present study were to determine the mechanisms of post-stroke action slowing (using validated, highly specific simple reaction time (SRT) and tapping tests) and identify its imaging determinants (using multivariate lesion-symptom mapping (mLSM)). Methods: Action speed in the GRECogVASC cohort was assessed using finger tapping and SRT tests performed with both hands and analyzed using previously validated indices. Imaging determinants were identified using validated mLSM analyses and disconnection analysis and compared to those of an fMRI activation meta-analytic database. Results: Both the tapping time and SRT were 10.7% slower for the 394 patients (p = 0.0001) than for the 786 controls, without a group × test interaction (p = 0.2). The intra-individual distribution curve was characterized by a rightward shift with an unaltered attentional peak. The mLSM analyses showed tapping to be associated with lesions in the frontostriatal tract (p = 0.0007). The SRT was associated with lesions in the frontostriatal tract (p = 0.04) and the orbital part of F3 (p = 0.0001). The SRT-tapping index was associated with lesions in the orbital part of F3 (p = 0.0001). All lesions were located in the right hemisphere only and were responsible for the disconnection of several structures involved in motor preparation, initiation, and speed. A comparison with fMRI activation meta-analytic data highlighted mostly the same regions, including the orbital part of F3, the ventral and dorsal parts of F1, and the premotor and cingulate regions in the right hemisphere. Discussion: Our results confirm the marked impairment of action speed in stroke and show that the primary mechanism is motor slowing and that it is related to lesions in the right frontostriatal tract. A deficit in sustained alertness accounted for action slowing in the subgroup with lesions in the right orbital part of F3. Our SRT and mLSM results were in accordance with the fMRI activation data. Thus, stroke induces slowing in the broad network associated with SRT tasks by disrupting the frontostriatal tract and, to a lesser extent, other sites involved in attention. Highlights: Poststroke action slowing is mainly secondary to motor slowing. It is mainly due to frontostriatal tract lesion. Attentional impairment is less frequent and secondary to right F3 lesion.